Radioactivity of long-lived gamma emitters in egg - Hamid ramazanian; Tareq Alrefae (Kuwait Journal of Science)
Radioactivity in egg was investigated. The targeted radionuclides were the long-lived gamma emitters 228Ra, 226Ra, and 40K. Measurements were carried out using a high purity germanium detector. The calculated annual effective dose due to egg consumption was 79 μSv yr-1, which forms 1/4 of the 290 μSv yr-1 world average ingestion exposure from natural sources. Hence, no radiological hazards exist from egg consumption due to the presence of the investigated radionuclides.